1H NMR and 13C NMR characterization of n-heptane extraction of low-temperature coal tar reacted with formaldehyde. Issue 12 (17th June 2020) - Yao, Qiuxiang; Kong, Xiangxi; Dai, Xiaomin; Gao, Junwen; Wang, Rucheng; Zhang, Yujuan; Sun, Ming; Ma, Xiaoxun
ABSTRACT: The optimum conditions of toluene insoluble-quinoline soluble fraction (TI-QS) obtained by n -heptane Soxhlet extraction residue of low-temperature coal tar (H-CT) reacted with formaldehyde were determined. And 1 H NMR and 13 C NMR were employed to analyze the structure of H-CT and its reaction products (P-H-CT). The results show that the yield of TI-QS is the largest at the reaction conditions as follows: reaction temperature 90°C, reaction time 3 h and with 3 wt% addition of catalyst. The contents of aliphatic carbon and aromatic carbon bonded to oxygen are higher in H-CT. The contents of aliphatic CH3 carbon and aromatic CH3 carbon are higher in P-H-CT. The content of methylene decreases and the content of methane increases, but the decrease of methylene is larger than the increase of methane; therefore, CH/CH2 carbon decreases slightly. The content of Hγ is 0.10 wt%, and the contents of Hα and Hβ are all 0.25 wt% in P-H-CT. The Hγ, Hα and Hβ ratios of P-H-CT to H-CT are small, displaying a lower branched degree of P-H-CT.